Weighted distance iteration matrix CFAR detector in Sea clutter. Issue 10 (2nd September 2020) - Ye, Lei; Jian, Fusheng; Yang, Yong; Zhang, Wei; Yang, Qiang; Chen, Qiushi
Abstract : High‐frequency surface wave radar (HFSWR) is an effective method for detecting and monitoring the targets on the ocean surface and above. To improve the detection performance of HFSWR, a new detector is proposed by applying weighted distance iteration (WDI) processing to the joint domain localised (JDL) matrix constant false alarm rate (CFAR) detector. Based on information geometry theory and Riemannian manifold, the proposed detector uses multi‐dimensional information (azimuth, Doppler velocity and range information) of the signal to effectively find the target that has drowned in sea clutter and uses WDI‐processing technique to suppress the clutter. The experimental results are given to show the superiority of the proposed detector. Compared with cell average CFAR detector and JDL matrix CFAR detector, the proposed detector improves the detection performance effectively.